Synthesis of ZnO nanospheres for water treatment through adsorption and photocatalytic degradation: Modelling and process optimization. (December 2019) - Zaidi, Zakiullah; Siddiqui, Sharf Ilahi; Fatima, Bushra; Chaudhry, Saif Ali
Graphical abstract: Highlights: This study reports the fabrication of ZnO nanospheres. ZnO nanospheres were prepared via hydrothermal method. ZnO nanospheres removed Bismarck brown R dye from water through adsorption. ZnO nanospheres having 3.2 eV band gap worked as photocatalyst for Bismarck brown R. Langmuir isotherm gave 10.309 mg/g maximum adsorption capacity of ZnO nanospheres. Abstract: Here, ZnO nanospheres preparation via simple hydrothermal method has been reported. The physicochemical properties of ZnO nanospheres have been analyzed extensively by using PXRD, SEM, TEM, and DRS techniques. The prepared ZnO nanospheres were utilized as an efficient adsorbent for Bismarck brown (BBR) dye, in batch mode to evaluate the adsorption capacity. The effect of ZnO dosage, concentration of BBR, contact time, pH of solution, and temperature has been studied in detail. Isotherm and kinetic studies have suggested that the BBR adsorption followed Langmuir isotherm giving 10.309 mg/g monolayer capacity and pseudo-second order kinetics with rate constant 0.041 g/mg/min. The free energy values, −4.831, −5.888, and −5.918 kJ/mol at 27, 35, and 45 °C, respectively, confirmed spontaneity the physical nature of BBR sorption onto ZnO nanospheres. The band gap of the prepared ZnO nanospheres was evaluated as 3.22 eV by using Kubelka-Munk equation from DRS technique which established semiconducting nature. The water treatment through the photocatalytic degradation was also performed with and without ZnO nanospheres. The kinetic plot for the photocatalytic degradation of dye indicated the fitting of data to the pseudo-first order kinetic model. Therefore, the synthesized ZnO nanospheres can be photoactive as well as effective adsorbent for the removal of organic water pollutants.